(untitled) (Journal of Face Aesthetics, 2021)
Discoid lupus erythematosus is the most common clinical manifestation of lupus erythematosus. Characteristic features are erythematous plaques with follicular hiperkeratosis, clearly demarcated from surrounding skin, that resolve with atrophy and scarring, leading to significant aesthetic defects. The consequence of involving the scalp is cicatrical alopecia. On the ground of long lasting, untreated lesions squamous cell carcinoma (SCC) may develop. On the other hand SCC remains in the circle of DLE differentiation. We present diagnostic and therapeutic difficulties associated with DLE.